The Iron Road in the Prairie State : The Story of Illinois Railroading - Cordery, Simon, 1960- (Book collections on Project MUSE., 2016)
In 1836, Abraham Lincoln and Stephen Douglas agreed on one thing: Illinois needed railroads. Over the next fifty years, the state became the nation's railroad hub, with Chicago at its center. Speculators, greed, growth, and regulation followed as the railroad industry consumed unprecedented amounts of capital and labor. A nationwide market resulted, and the Windy City became the site of opportunities and challenges that remain to this day. In this first-of-its-kind history, full of entertaining anecdotes and colorful characters, Simon Cordery describes the explosive growth of Illinois railroads and its impact on America. Cordery shows how railroading in Illinois influenced railroad financing, the creation of a national economy, and government regulation of business. Cordery's masterful chronicle of rail development in Illinois from 1837 to 2010 reveals how the state's expanding railroads became the foundation of the nation's rail network.